Limites e possibilidades do uso de portais municipais para promoção da cidadania: a construção de um modelo de análise e avaliação - Vaz, José Carlos (2003)
This research focuses on citizenship as a potential or elfective municipal portal ontput. A comprehensive municipal portal analysis and evalution model (MAAP-M) was created to evaluate municipal portais contributions towards citizenship strengthening. Model validation uses São Paulo Municipality's portal case study to show how useful such technology can be. This research also includes an exploratory research about services and information delivery by municipal portals. Both the exploratory research and the São Paulo case study can also serve as input to analyse Brazilian municipal portal usage pattern. Portais are evaluated as useful touls to improve citizenship, but they are always influenced by special conditions related to technological and non-technological factors.